Photo-Conductivity Measurements of Single Line Structure of Poly (3-hexylthiophen) Patterned Film in Submicro-Meter Range by Conducting Atomic Force Micro scope - SAWADAISHI, Tetsurou; SHIMOMURA, Masatsugu; HASHIMOTO, Yuichi; IMO, Kuniharu (KOBUNSHI RONBUNSHU, 2002)
A patterned film of a conducting polymer, poly (3-hexylthiophene) (PHT) was prepared by a simple casting method on its microstructured Au-electrode. Line structures (1.5-3μm wide, 70 nm height) lie in a uniform array at regular intervals in this film. Electronic conductivity between a conducting cantilever and the micro-structured electrode on the substrate through one thin line of PHT was measured by conducting atomic force microscopy (conducting AFM). Topographic image and current mapping showed that the current flowed through only the PHT line. Large current was observed at the boundary surface of the micro electrode. Electric current decreased in proportion to the distance between the cantilever and the micro electrode over 500 nm. This indicates that ohmic conductivity was dominant in the thin line of PHT. When the conventional conducting AFM was modified with an optical filter, photo conductivity could be measured by irradiation of laser light to excite the polymer thin line. Irradiation of the light (λ=488nm) increased the electric current through the thin line of PHT. The electric conductivity of the line structure in the patterned film of PHT was higher than that of the uniform cast film due to higher molecular organization of PHT in the thin line structure.